The Development of the Components of the Linear Measurement Concept among the Pupils of the First Grade of Primary School - Milica D. Antić; Olivera J. Đokić (University of Belgrade, Teacher Education Faculty, 2018)
Results of the international research, for example TIMSS, show that student's understanding of geometrical contents is often below the level in comparison the contents of other areas of mathematics. For revealing the cause, we focused on the beginning of primary school mathematical education, searching for the basic results of the lower achievements of students in this field. We studied achievements o students of the first grade in the field of Measuring and Measurements, with the stress on measuring length. The aim of the paper was to determine in which extent the students of the first grade were successful in mastering the term of measuring length, which is composed on components upon which the procedure of measuring is established. The following components are in question: dividing, sequencing the measuring unit, transitivity, conservation, accumulation of the distance and relation between the measuring number and measuring unit. Descriptive method was used. The basic conclusion of the paper are that there is a huge gap concerning adoption of the term measuring length and the components out of which it is composed, as well as that the existing mathematics syllabus in those days, which influenced the work of teachers and authors of the course book did not offer sage basis and support to teachers' work. New syllabus for the first grade contains some changes in accordance with the results of our research. Nevertheless, for the further research we suggest observing the forming of the term measuring length through all its components, and this would be through practical stimulation and special experience of students, as well as through examples in which the students would observe the relations of the objects in space, compare the sizes of the bodies, etc.